2013
DOI: 10.1097/dcr.0b013e3182a4adfb
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Recovery of the Injured Anal Sphincter After Repair and Injection of Myogenic Stem Cells

Abstract: In vivo functional studies show recovery of anal sphincter pressures and electromyography to preinjury levels by day 14 in the myogenic stem cell group but not controls. At 4 weeks, all electromyography parameters returned to baseline irrespective of group. Restoration of function may be accelerated by the transplantation of myogenic stem cells and associated trophic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…In our study, the anal pressures were comparable with the other animal studies although there are slight variations—possibly due to different techniques (balloon vs. double‐triple‐lumen‐catheter, electrical stimulation vs. spontaneous contraction) and different size of the anal canal in different species 13, 16, 19. Salcedo et al stated that rat anal pressures tend to return to baseline after sphincterotomy at 4 weeks even without intervention, but this does not occur after pudendal nerve transection 42.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our study, the anal pressures were comparable with the other animal studies although there are slight variations—possibly due to different techniques (balloon vs. double‐triple‐lumen‐catheter, electrical stimulation vs. spontaneous contraction) and different size of the anal canal in different species 13, 16, 19. Salcedo et al stated that rat anal pressures tend to return to baseline after sphincterotomy at 4 weeks even without intervention, but this does not occur after pudendal nerve transection 42.…”
Section: Discussionsupporting
confidence: 84%
“…It has been suggested that stem cell transplantation may facilitate endogenous repair even in patients with advanced age and comorbidities who have compromised repair function [13]. Therefore, stem cell therapy would be especially useful in patients with compromised anal sphincter function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to use the anesthetic ketamine/xylazine mixture, because it was the one we found to provide more stable registries. This mixture was also used by Zutshi and colleagues[ 29 , 34 - 36 ], but other authors have employed ketamine with better results than ours[ 37 ].…”
Section: Discussionmentioning
confidence: 89%
“…The exact mechanisms, histomorphologic and functional changes of disrupted sphincter muscles in response to myoblasts, are being studied using animal models. [121-123] In humans, similar regenerative therapy with autologous cells injected into the urethral sphincter in patients with stress urinary incontinence appears to be beneficial in small investigational studies. [124,125] The pilot study has been conducted to evaluate the clinical efficacy of the autologous myoblast cell injection (cultured and harvested from the pectoralis muscle) in women with symptomatic FI due to disrupted EAS from obstetric trauma.…”
Section: Investigational Treatment Optionsmentioning
confidence: 99%